2014
DOI: 10.1111/vde.12188
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of superficial epidermal adhesion molecules in an experimental dog model of acute atopic dermatitis skin lesions

Abstract: These observations suggest that HDM allergens, via proteolytic digestion and/or because of induced allergic inflammation, affect the expression and possible function of corneodesmosomal and tight junction proteins. Ensuing intercellular junction alterations might promote an abnormally increased penetration of allergens through the epidermis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 12 publications
0
18
1
Order By: Relevance
“…A study in atopic research dogs reported that the integrity of corneodesmosomal and TJ proteins, including claudin‐1, was discontinuous in acute challenged atopics compared to vehicle‐applied atopic dogs . The authors did not compare these findings with normal dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in atopic research dogs reported that the integrity of corneodesmosomal and TJ proteins, including claudin‐1, was discontinuous in acute challenged atopics compared to vehicle‐applied atopic dogs . The authors did not compare these findings with normal dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies exist on expression of TJ proteins in canine AD. In one study, TJ protein expression on patch test sites was reported, but no comparison with normal dogs was done . Additionally, another study investigated TJ proteins in atopic and normal dogs with immunohistochemistry (IHC)…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have assessed select immune markers, primarily in experimental systems. In animal models, HDM showed early Th2/Th22 skewing and upregulation of S100A8/9/12 at 6 hours post‐application, with parallel barrier changes (epidermal hyperplasia, decreased differentiation, increased TEWL) . In ex vivo cultures, HDM induced both Th2 (IL‐4, CCL17, TSLP) and Th17/Th22 markers, while in human keratinocytes co‐treated with IL‐17A, HDM showed robust increases in S100A8/9 expression .…”
Section: Introductionmentioning
confidence: 95%
“…In animal models, HDM showed early Th2/ Th22 skewing and upregulation of S100A8/9/12 at 6 hours postapplication, with parallel barrier changes (epidermal hyperplasia, decreased differentiation, increased TEWL). [23][24][25][26][27][28] In ex vivo cultures, HDM induced both Th2 (IL-4, CCL17, TSLP) and Th17/Th22 markers, while in human keratinocytes co-treated with IL-17A, HDM showed robust increases in S100A8/9 expression. [29][30][31] In AD patients, HDM upregulated inflammatory dendritic epidermal cells/ IDECs 72 hours after sensitization.…”
mentioning
confidence: 99%
“…This suggests that PKP2 expression may be altered in the skin of GSDs carrying the risk variants compared to dogs without the risk variants. Expression patterns of the adhesion molecules corneodesmosin, desmoglein‐1, desmocollin‐1, claudin‐1 and E‐cadherin were compared in dog skin with acute CAD lesions and healthy skin from the same dogs, and the most striking differences were found for corneodesmosin and claudin‐1 . This implies that differential expression of desmosomal proteins are involved in the pathogenesis of atopic dermatitis (AD) in dogs and that PKP2 could also contribute to the pathogenesis of CAD.…”
Section: Introductionmentioning
confidence: 99%